The Impact of Diet and Physical Activity on Bone Health in Children and Adolescents - Proia, Patrizia; Amato, Alessandra; Drid, Patrik; Korovljev, Darinka; Vasto, Sonya; Baldassano, Sara (Frontiers in Endocrinology, 2021)
There is growing recognition of the role of diet and physical activity in modulating bone mineral density, bone mineral content, and remodeling which in turn can impact bone health later in life. Adequate nutrient composition could influence bone health and help to maximize peak bone mass. Therefore, children’s nutrition may have life-long consequences. Also, physical activity, adequate in volume or intensity may have positive consequences on bone mineral content and density and preserve bone loss in adulthood. Most of the literature that exists for children, about diet and physical activity on bone health, has been translated from studies conducted in adults. Thus, there are still many unanswered questions about what type of diet and physical activity may positively influence skeletal development. This review focuses on bone requirements in terms of nutrients and physical activity in childhood and adolescence to promote bone health. It explores the contemporary scientific literature that analyzes the impact of diet together with the typology and timing of physical activity that could be more appropriate depending on whether they are children and adolescents to assure an optimal skeleton formation. A description of the role of PTH and gut hormones (GIP, GLP-1, GLP-2) as potential candidates in this interaction to promote bone health is also presented.